English Phraseology: Integration with Terminology Science - Elena Nikulina (Journal of Language and Education, 2015)
The article is devoted to the study of English semi-idioms (a term suggested by A. Kunin), units with both terminological and metaphorical meanings. These units were studied from different angles but here their dual nature is viewed through the possibility of providing an experiment. The paper shows how a linguistic experiment can reveal not only the meaning of some unit, but the peoples’ attitude towards the use of these phrases, their individual level of understanding, interpreting and realising. As cognition is very important in the understanding of semantics, as well as a new perspective in the study of phraseology, a synergetic approach as well as a cognitive one is becoming one of the ways to scrutinising the nature of terminological phraseological units. The paper focuses on the possible ways of showing that terms can develop metaphorical meanings though sometimes people have no ideas of the etymology of some units. An experiment to show the dual nature of such units as terminological phraseologisms was provided on the bases of a specially created questionnaire. The result of the experiment proved that some terms can acquire new metaphorical meanings and function in the language and speech as phraseological units. The results of the experiment as well as various references to the matter of the study – semi-idioms – may turn to be useful in language studies, learning English as a second language, investigating English Terminology and Phraseology.